COMMUNICATIVE AND FUNCTIONAL FEATURES OF MEDICAL TEXTS IN ENGLISH AND UZBEK (KONFERENSIYA, 2025)
This article examines the communicative and functional features of medicaltexts in English and Uzbek. Medical texts serve multiple purposes, includingproviding information, giving instructions, expressing professional evaluation,maintaining communication, clarifying terminology, and linking language to factualreality. Examples illustrate the use of specialized terminology, native equivalents,compound forms, and patient-oriented expressions. The study highlights theimportance of these features for translation, clinical practice, patient education, andterminology standardization. Findings show that English texts are concise and rely oninternational terminology, while Uzbek texts often provide additional explanation forbetter patient understanding, demonstrating the role of cultural adaptation andfunctional purpose in medical communication